Language Differences in the Quran and Their Implications for Arabic Teaching in Indonesia - Chamidah, Dewi; Sarif, Abdullah; Maf'udah, Syafiyatul (Arabiyatuna: Jurnal Bahasa Arab, 2023)
This research aims to discuss the concepts and forms of differences in Arabic in the Koran and to uncover the facts about whether these differences have implications for Arabic language learning in Indonesia. The Arabic language that we study is not only a foreign language but also a noble language due to the language of the Koran. Even though they both use the same language, there are several differences between the Arabic language in the Koran and the one studied. This research used a library research method in a way that collected information and data with the help of various kinds of literature related to the research theme. The results of this research fell into: 1) The language contained in the Qur'an is the same, but the meanings and language used are different because the Qur'an was created so that no one could compare it. 2) Even though the Arabic language in the Koran and learning are different, this is not an obstacle to the language learning process in Indonesia; it will give Arabic its own special features. 3) The existence of differences in Arabic in the Qur'an has positive implications for variations in the word meanings in terms of both synonyms and antonyms; this will provide a richness of language in the application and learning of the language itself. Â